Replacing temperature targets by subsidiary targetsː How accurate are they? – Overshooting vs. economic losses - Lukas Stein; Mohammad Mohammadi Khabbazan; Hermann Held (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
This article investigates the trade-off between increasing welfare losses and increasing peak-warming if a temperature target is reformulated as a subsidiary concentration or cumulative emissions target. We apply a welfare maximizing integrated assessment model for a deterministic cost-effectiveness analysis to identify the associated costs of a certain climate target.We find that the use of subsidiary targets, a common practice in integrated climate modeling, increases losses by at least 12% for time-limited concentration targets that allow for a peak before concentration stabilizes. For all-time concentration targets we find that losses increase at least by 50%. Under all-time cumulative emissions targets losses rise by at least 20%. If the subsidiary all-time targets are forced to have equal cost as their parental maximum-warming target, all-time cumulative emissions (concentration) targets overshoot by more than 0.1°C (0.2°C). Generally, among the investigated subsidiary targets, we find all-time cumulative emissions targets and time-limited concentration targets to behave most similar to the parental temperature targets.
Keywords: 330; Klimaschutz; Politisches Ziel; Soziale Kosten; Entscheidungstheorie; Welt